Islamising Indonesia The Rise of Jemaah Tarbiyah and the Prosperous Justice Party (PKS) - Machmudi, Yon (Islam in Southeast Asia, 2008)
The Prosperous Justice Party (PKS) is the most interesting phenomenon in contemporary Indonesian politics. Not only is it growing rapidly in membership and electoral support, it is also bringing a new and markedly different approach to Islamic politics, one which has no precedent in Indonesian history. Understanding PKS and analysing its political behaviour presents challenges to scholars and observers. This is partly due to the fact that the party represents a new trend within Indonesian Islam which has few parallels with preceding movements. Yon Machmudi has rendered us a valuable service. In this book, he provides a thoughtful and authoritative context for viewing PKS. He critiques the existing categorisations for Indonesian Islam and points to their inadequacy when describing the PKS and the campus-based Tarbiyah movement from which it sprang. He reworks the santri typology, dividing it into convergent, radical and global substreams. This offers new possibilities for explaining the PKS phenomenon and assists in differentiating between various types of Islamic revivalism in contemporary Indonesia. It also allows a more understanding of the accommodatory stance which PKS has towards the state and other political forces. Yon's text provides a good overview of the development of PKS from its Tarbiyah movement origins to its impressive success at the 2004 general elections. It considers the party's attitude towards the issues of sharia implementation and community welfare and closes by examining the future challenges facing PKS. It is a well written and authoritative account from a scholar who has done wideranging research on the party.